1996
DOI: 10.1103/physrevlett.76.4062
|View full text |Cite
|
Sign up to set email alerts
|

Fingerlike Aggregates in Thin-Layer Electrodeposition

Abstract: Electrodeposition experiments conducted in a thin-layer horizontal cell containing a nonbinary aqueous electrolyte prepared with cupric sulfate and sodium sulfate gave rise to fingerlike deposits, a novel and unexpected growth mode in this context. Both the leading instability from which fingers emerge and some distinctive features of their steady evolution are interpreted in terms of a simple model based on the existing theory of fingering in fluids. [S0031-9007(96)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…Many authors have reported the quasi-two-dimensional growth of metallic electrodeposits, particularly for copper [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] and zinc [16][17][18][19][20][21][22][23][24][25], and other metals [26][27][28][29][30][31]. The typical patterns observed so far are stringy, dendritic, open ramified, dense branching morphology (DBM), and diffusion limited aggregation (DLA), etc, depending on the growing conditions, such as applied voltage, concentration of the solution and thickness of the electrolyte layer.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Many authors have reported the quasi-two-dimensional growth of metallic electrodeposits, particularly for copper [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] and zinc [16][17][18][19][20][21][22][23][24][25], and other metals [26][27][28][29][30][31]. The typical patterns observed so far are stringy, dendritic, open ramified, dense branching morphology (DBM), and diffusion limited aggregation (DLA), etc, depending on the growing conditions, such as applied voltage, concentration of the solution and thickness of the electrolyte layer.…”
Section: Introductionmentioning
confidence: 95%
“…The typical patterns observed so far are stringy, dendritic, open ramified, dense branching morphology (DBM), and diffusion limited aggregation (DLA), etc, depending on the growing conditions, such as applied voltage, concentration of the solution and thickness of the electrolyte layer. Other types of patterns, such as finger-like [12][13][14][15], and mesh-like [28], are also known. While the DLA [32,33] pattern appears for both zinc [16][17][18][19] and copper deposits [1,2], especially when the voltage or concentration is reduced, the dendritic pattern is easily observed for zinc, and most observations for copper have ramified patterns.…”
Section: Introductionmentioning
confidence: 99%
“…The morphology has much variety; for example, homogeneous, dendritic, fractal, open-ramified, finger-like and other complex structures appear depending on applied voltage and electrolyte concentration [1][2][3][4][5][6][7][8][9]. For instance, Sawada et al [1] showed the transition from dendritic to disordered ramified patterns with decreasing electrolyte concentration in the electrodeposition of Zn from a thin layer of ZnSO 4 solution confined between Plexiglas disks.…”
Section: Introductionmentioning
confidence: 97%
“…Gonzalez et al [4] studied the effect of viscosity of the electrolyte on the electrodeposits from the viewpoint of fluid dynamics (i.e., Navier-Stokes equation). In addition to the above studies, pattern formation in electrodeposition has been studied experimentally [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Convection certainly increases ECD complexity and it is natural to try to reduce its influence [27,28,12,13,29,30,22] ECD in a cell in a vertical position relative to gravity and with the cathode above the anode is often used as an example of a convection reduced ion transport regime. This problem was analyzed in Huth et al [12]; these authors found that the invasion of the cell by the gravity induced rolls can be avoided while electroconvection remains.…”
Section: Introductionmentioning
confidence: 99%